PID Controller Design for Two Tanks Liquid Level Control System Using Matlab - Mostafa Abdul Fellani; Aboubaker M. Gabaj (International Journal of Electrical and Computer Engineering (IJECE), 2015)
The industrial application of Coupled Tank System (CTS) is widely used especially in chemical process industries. The control of liquid level in tanks and flow between tanks is a problem in the process technologies. The process technologies require liquids to be pumped, stored in tanks, and then pumped to another tank systematically. This paper presents development of Proportional-Integral-Derivative (PID) controller for controlling the desired liquid level of the CTS. Various conventional techniques of PID tuning method will be tested in order to obtain the PID controller parameters. Simulation is conducted within MATLAB environment to verify the performances of the system in terms of Rise Time (Ts), Settling Time (Ts), Steady State Error (SSE) and Overshoot (OS). The trial and error method of tunning will be implemented and all the performance results will be analyzed using MATLAB. It has been demonstrated that performances of CTS can be improved with appropriate technique of PID tuning methods.